PENGARUH DANA TRANSFER KE DESA TERHADAP NILAI INDEKS DESA MEMBANGUN DI KOTA BANJAR PROVINSI JAWA BARAT - Dyah Yuni Lestari; Muhammad Imron; Mintarti Indartini (JAMER : Jurnal Akuntansi Merdeka, 2025)
One of the sources of village income is transfer funds, which consist of village funds, tax and retribution sharing, village fund allocations, and provincial financial assistance. The use of that budget underlies the birth of the Village Development Index, which is one of the instruments to capture the development of village independence. Banjar City in West Java Province is the only city in West Java Province that has villages with relatively high Indeks Desa Membangun scores. This research aims to determine the effect of transfer funds on the Developing Village Index in the relevant year.Data were obtained from the website of the Ministry of Development of Disadvantaged Villages and Transmigration for the year 2024. Data analysis was conducted using multiple linear regression with Minitab 21 software. The analysis results indicate that village funds do not affect the Developing Village Index, whereas tax and retribution sharing as well as village fund allocation significantly affect the Developing Village Index.